The Effect of STEM Applications on the Scientific Creativity of 9th-Grade Students - Seyide Eroglu; Oktay Bektas (Journal of Education in Science, Environment and Health)
The study aims to investigate the effect of STEM applications designed for the atomic system and periodic system unit on the scientific creativity of 9th-grade students. The exploratory sequential design, mixed research, is used in the study. The pretest-posttest quasi-experimental design has been preferred for the quantitative part of the study and the phenomenology design for the qualitative part. The study lasted 12 weeks during the first semester of the 2016-2017 academic year. The sample of the study consists of 133 ninth-grade high school students. The study uses an experimental and a control group. The Scientific Creativity Test was used as a data collection tool. Quantitative data were analyzed using the independent samples t-test through the package program SPSS 22. On the other hand, the qualitative data were analyzed using content analysis. As a result of the study, a statistically significant difference was observed to exist between the groups in terms of scientific creativity in favor of the experimental group. In addition, the participants were determined to have put forward many different and extraordinary thoughts with different perspectives. Based on these results, including activities that will improve students’ scientific creativity in chemistry lessons is suggested.